Occurrence and antimicrobial resistance of non-typhoidal Salmonella isolates belonging to layer breeds and the farm environment - AASTHA NAGPAL; MAANSI; A K UPADHYAY (Indian Journal of Animal Sciences)
This study assessed the occurrence and antimicrobial resistance of NTS organisms isolated from faecal, caecal and environmental samples of five-layer breeds [Uttara fowl, Kadaknath, Rhode Island Red (RIR), White Leghorn and Australorp] raised in an organized farm. A total of 470 samples were examined using the culture method, followed by biochemical and molecular confirmation of the isolates. All Salmonella strains were tested for their susceptibility to the antibiotics using the disk diffusion method. The overall occurrence of NTS was 4.89% (23/470). RIR showed a highest occurrence (17.58%), followed by Uttara fowl (2.73%) and Kadaknath (1.82%). Water samples had the highest occurrence (10.77%), followed by poultry faeces (6.67%) and caeca (6.0%). On serotyping, a single serovar viz. Salmonella Typhimurium (91.3%) was found to be circulated on the farm. The highest resistance was observed for erythromycin (100%), followed by ampicillin (65.22%) and nalidixic acid (56.52%). About 78.26% of isolates were multidrug-resistant (MDR). The multiple antibiotic resistance (MAR) index ranged from 0.15-0.69. The study confirmed the presence of MDR S. Typhimurium in the breeds and the farm environment, warranting strict control and surveillance.